Leaf classification by feature extraction using CNN - Bhuiyan, Md. Mazharul Islam; Nowshin, Jakia; Jaheen, Atkiya (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.